Implementasi Pembelajaran Al -Qur’an Hadis secara Mendalam Untuk Meningkatkan Literasi Religius dan Akhlak Siswa - Riska Febriani; Syifa Ullinnas; Sumiarti (Laskar Karya, 2025)
This study aims to analyze the implementation of deepened learning of the Qur’an and Hadith and its impact on enhancing religious literacy and character formation among students at SMPN 1 Patamuan, West Sumatra. The background of the research arises from the low interest in reading the Qur’an, limited understanding of Hadith, and the insufficient internalization of moral values in students’ daily lives. Using a descriptive qualitative approach, this study involved Qur’an–Hadith teachers, students, and school administrators as key informants through classroom observations, in-depth interviews, and documentation analysis. Data were examined using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The findings indicate that deepened learning of the Qur’an and Hadith through methods such as tadabbur, simple interpretation, value-based discussions, and religious practices significantly contributes to students’ spiritual, moral, and social development. Activities such as tadarus, short sermons, character journals, and social projects help students internalize Qur’anic values and apply them in their behavior. Moreover, teacher role modeling, a religious school culture, and collaboration with families strengthen the process of character formation. This study concludes that reflective, contextual, and practice-oriented Qur’an–Hadith learning is an effective strategy to improve students’ religious literacy and foster noble character at the junior secondary school level. These findings are expected to serve as a reference for schools in developing more transformative and applicable Islamic education models.